Global and local effects in lipid-mediated interactions between peripheral and integral membrane proteins - Rostovtseva, Tatiana K.; Hoogerheide, David P.; Milhizer, William A.; Bezrukov, Sergey M. (Frontiers in Molecular Biosciences, 2025)
Amphitropic proteins (APs) are a subfamily of water-soluble peripherally membrane-bound proteins that interact directly with the lipid membrane rather than with intrinsic membrane proteins and are therefore strongly influenced by membrane properties. When an AP interacts with a membrane containing an integral membrane protein, a ternary protein-lipid-protein system is created. Even in the absence of direct interactions between the amphitropic and integral proteins, the two proteins can affect each other by modifying lipid membrane properties, either at the global (i.e., whole-membrane) or local (i.e., confined to a small area around the bound or integrated protein) scale. These lipid-mediated protein-protein interactions are indirect and, therefore, difficult to elucidate; independent experimental data are required to report on each individual interaction to comprehend the whole system. Examples for which comprehensive data are available are remarkably rare. In this article, we describe how these difficulties could be surmounted by using the channel-forming integral membrane protein gramicidin A (grA) reconstituted in a planar lipid membrane and exposed to the amphitropic proteins dimeric tubulin or α-synuclein. Importantly, there are no known direct interactions between these APs and grA, thus revealing the role of the lipid membrane. Here, grA serves a dual role. First, grA reports on the global properties of the lipid membrane; grA results, combined with the well-understood tubulin-lipid interaction, yield a complete picture of the mutual effect of tubulin binding on the lipid membrane. Second, the presence of the grA conducting dimer alters the local membrane curvature and creates binding sites for tubulin in an otherwise inert membrane composition.